Factors Influencing Students’ Speaking Anxiety in Class Presentation of Undergraduate English Majors at The University of Bengkulu - Putri, Vania Sugondo; Jayanti, Fernandita Gusweni; Puspa, Adelia (Journal of English Education and Teaching, 2025)
Speaking anxiety refers to feelings of worry, tension, and nervousness related to one’s ability to speak in front of an audience. Class presentations, a common speaking activity in academic settings, often trigger this anxiety among students. This research aims to investigate the levels and factors influencing students’ speaking anxiety during class presentations. To achieve these aims, a mixed-method approach was used. Data were collected through a questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz et al. (1986), along with follow-up interviews. The participants were 178 students from the English Education Study Program at the University of Bengkulu. Additionally, five students were interviewed to gain deeper insights into the factors causing anxiety. The results showed that 19 students (10%) were in the “very relaxed” category, 46 students (26%) in the “relaxed,” 65 students (37%) in the “mildly anxious,” 25 students (14%) in the “anxious,” and 23 students (13%) in the “very anxious” category. Most students experienced a mildly anxious level. The study also identified three main factors that significantly contribute to students’ anxiety: communication apprehension, test anxiety, and fear of evaluation. These findings highlight that speaking anxiety is common among students, especially during class presentations. Also, provide lecturers with valuable insights for developing strategies to help students improve their speaking confidence and performance.